2009
DOI: 10.1897/ieam_2009-045.1
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Special Series: Science‐Based Guidance and Framework for the Evaluation and Identification of PBTs and POPs

Abstract: There is a growing sense of urgency among scientists and environmental policy-makers concerning the need for improving the scientific foundation supporting international regulations for identifying and evaluating persistent, bioaccumulative, and toxic (PBT) substances and persistent organic pollutants (POPs) in the environment. The current national and international regulations define PBTs and POPs in terms of fairly strict criteria that are based on the state of the science in the late 1970s and early 1980s. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Thomann (1989) and Qiao et al (2000) observed that at naturally occurring food-to-water concentration ratios, uptake of highly lipophilic chemicals (i.e., log K ow [ 6) from water into biota is generally low compared with uptake by way of consumption of contaminated foodstuffs, with the importance of dietary uptake increasing with increasing K ow values. A recent review resulting from an international Pellston workshop (Klecka et al 2009) proposed a flowchart for the assessment of bioaccumulation criteria. The flowchart indicates that a field trophic magnification factor (TMF) value is the best criterion by which to determine chemical bioaccumulation, followed by a BMF value, and then a BCF value, with an estimate based on physicochemical parameters generating the lowest degree of confidence ).…”
Section: Resultsmentioning
confidence: 99%
“…Thomann (1989) and Qiao et al (2000) observed that at naturally occurring food-to-water concentration ratios, uptake of highly lipophilic chemicals (i.e., log K ow [ 6) from water into biota is generally low compared with uptake by way of consumption of contaminated foodstuffs, with the importance of dietary uptake increasing with increasing K ow values. A recent review resulting from an international Pellston workshop (Klecka et al 2009) proposed a flowchart for the assessment of bioaccumulation criteria. The flowchart indicates that a field trophic magnification factor (TMF) value is the best criterion by which to determine chemical bioaccumulation, followed by a BMF value, and then a BCF value, with an estimate based on physicochemical parameters generating the lowest degree of confidence ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, identifying substances as potential PBT or POP candidates relies mainly on determining if specific properties of a chemical exceed threshold values for each property related to PBT behavior (commonly, half-life in various compartments for P, BCF for B and a number of toxicity evidences for T) (Muir and Howard, 2006;Klecka et al, 2009;Moermond et al, 2011;Solomon et al, 2013). However, in the most recent papers (Moermond et al, 2011;Solomon et al, 2013) it was highlighted that there is no uniform PBT or vPvB assessment of chemicals, as various regulatory frameworks use different criteria for categorization.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario of not generally accepted and widely used rules, it is evident that the best approach for reliable PBT assessment is to be confident in the assignments obtained by agreement from different tools (a consensus approach). Klecka et al (2009) correctly highlighted that there is a fundamental difference in methods used to rank, as well as prioritize, chemicals for PBT or POP properties when compared with detailed PBT or POP assessment of chemicals that were already prioritized. "In this first, prioritysetting phase, rapid and efficient approaches should be used and, generally, will be developed to minimize the probability of potential false negative results.…”
Section: Introductionmentioning
confidence: 99%
“…The focus of our search was on PPPs but, where relevant, data for other substances were used to inform our analysis. The report and papers resulting from the Society of Environmental Toxicology and Chemistry (SETAC) POPs workshop held in 2008 [11], et seq., were particularly useful in this regard.…”
Section: Methodsmentioning
confidence: 99%